Dynamics and role of antibodies to Plasmodium falciparum merozoite antigens in children living in two settings with differing malaria transmission intensity. Issue 1 (2nd January 2016) - Kangoye, David Tiga; Mensah, Victorine Atanase; Murungi, Linda Muthoni; Nkumama, Irene; Nebie, Issa; Marsh, Kevin; Cisse, Badara; Bejon, Philip; Osier, Faith Hope Among'in; Sirima, Sodiomon Bienvenu; ,; Yaro, Jean-Baptiste; et al.
Highlights: Antibody dynamics and role in young the infants' low susceptibility to febrile malaria were investigated. No evidence for association of antibody titres with clinical protection was found. Evidence for consistently low antibody titres in high and low transmission areas. Other antibodies, other antibody-mediated mechanisms or other protecting factors may be operating. Abstract: Background: Young infants have reduced susceptibility to febrile malaria compared with older children, but the mechanism for this remains unclear. There are conflicting data on the role of passively acquired antibodies. Here, we examine antibody titres to merozoite surface antigens in the protection of children in their first two years of life in two settings with differing malaria transmission intensity and compare these titres to previously established protective thresholds. Methods: Two cohorts of children aged four to six weeks were recruited in Banfora, Burkina and Keur Soce, Senegal and followed up for two years. Malaria infections were detected by light microscopic examination of blood smears collected at active and passive case detection visits. The titres of antibodies to the Plasmodium falciparum recombinant merozoite proteins (AMA1-3D7, MSP1-19, MSP2-Dd2, and MSP3-3D7) were measured by enzyme-linked immunosorbent assay at 1–6, 9, 12, 15 and 18 months of age and compared with the protective thresholds established in Kenyan children. Results: Antibody titres were below the protective thresholds throughout the study period and we did not find any association with protection against febrile malaria. Antibodies to AMA1 and MSP1-19 appeared to be markers of exposure in the univariate analysis (and so associated with increasing risk) and adjusting for exposure reduced the strength and significance of this association. Conclusion: The antibody levels we measured are unlikely to be responsible for the apparent protection against febrile malaria seen in young infants. Further work to identify protective antibody responses might include functional assays and a wider range of antigens.